Fine-Tuning the Expression of Duplicate Genes by Translational Regulation in Arabidopsis and Maize - Wang, Sishuo; Chen, Youhua (Frontiers in Plant Science, 2019)
Plant genomes are extensively shaped by various types of gene duplication. However, in this active area of investigation, the vast majority of studies focus on the sequence and transcription of duplicate genes, leaving open the question of how translational regulation impacts the expression and evolution of duplicate genes. We explored this issue by comprehensively analyzing the ribo- and mRNA-seq data sets across six tissue types and stress conditions in Arabidopsis thaliana and maize (Zea mays). We dissected the relative contributions of transcriptional and translational regulation to the divergence in the abundance of ribosome footprint for both whole-genome duplicates and tandem duplicates. We found that the divergence in ribosome footprint abundance was largely programmed at the transcription level and that translational regulation plays more of a modulatory role. Intriguingly, translational regulation is characterized by its strong directionality, with the divergence in translational efficiency globally counteracting the divergence in mRNA abundance, indicating partial buffering of the transcriptional divergence between paralogs by translational regulation. Divergence in translational efficiency was associated with several sequence features. The faster-evolving copy in a duplicate pair was more likely to show lower ribosome footprint abundance, which possibly results from relaxed purifying selection compared with its paralog. A considerable proportion of duplicates displayed differential translational efficiency across tissue types and stress conditions, most of which were enriched in photosynthesis, energy production, and translation-related processes. Additionally, we constructed a database TDPDG-DB (www.plantdupribo.tk), providing an online platform for data exploration. Overall. our study illustrates the important roles of translational regulation in fine-tuning duplicate gene expression in plants.